Presentations and outcomes of familial hemophagocytic lymphohistiocytosis in the pediatric intensive care units (PICUs) - Alsohime, Fahad; Temsah, Mohamad-Hani; Alotaibi, Rawan M.; Alhalabi, Reham M.; AlEnezy, Sarah; Yousef, Aly Abdelrahman; Alzaydi, Abdullah Mohammed; Inany, Hussam Sameer; Al-Eyadhy, Ayman; Almazyad, Mohammed; Alharbi, Ali; Alsoqati, Abdulaziz Abdullah; et al. (Frontiers in Pediatrics, 2023)
Objectives: We aimed to describe Familial Hemophagocytic Lymphohistiocytosis (F-HLH) patients’ clinical features, intensive care courses, and outcomes. Methods: Multi-center retrospective cohort study of pediatric patients diagnosed with F-HLH from 2015 to 2020 in five tertiary centers in Saudi Arabia. Patients were classified as F-HLH based on their genetic confirmation of known mutation or on their clinical criteria, which include a constellation of abnormalities, early disease onset, recurrent HLH without other causes, or a family history of HLH. Results: Fifty-eight patients (28 male, 30 female), with a mean age of 21.0 ± 33.9 months, were included. The most common principal diagnosis was hematological or immune dysfunction (39.7%), followed by cardiovascular dysfunction in 13 (22.4%) patients. Fever was the most common clinical presentation in 27.6%, followed by convulsions (13.8%) and bleeding (13.8%). There were 20 patients (34.5%) who had splenomegaly, and more than 70% of patients had hyperferritinemia >500 mg/dl, hypertriglyceridemia >150 mg/dl and hemophagocytosis in bone marrow biopsy. Compared to deceased patients 18 (31%), survivors had significantly lower PT (p=041), bilirubin level of <34.2 mmol/L (p=0.042), higher serum triglyceride level (p=0.036), and lesser bleeding within the initial 6 hours of admission (p=0.004). Risk factors for mortality included requirements of higher levels of hemodynamic (61.1% vs. 17.5%, p=0.001) and respiratory (88.9% vs. 37.5%, p<0.001) support and positive fungal cultures (p=0.046). Conclusions: Familial HLH still represents a challenge in the pediatric critical care setting. Earlier diagnosis and prompt initiation of appropriate treatment could improve F-HLH survival.